MEDIA PEMBELAJARAN BAHASA INDONESIA BAGI PENUTUR ASING - Mustika, Samsul; Simamora, Pesta Junita; Rosliani, Rosliani (Unversitas Katolik Santo Thomas, 2023)
Today the use of Indonesian is in great demand by foreign nationals from different parts of the world. Indonesian can be a foreign language as well asan introduction for foreign speakers. In Indonesian learning for foreign speakers (BIPA), there are various aspects of learning. One aspect of BIPA learning is the use of learning media. Learning media is a set of educational means used to facilitate communication and learning with instructional purposes. Learning media can be very helpful in BIPA learning.